Spin injection and local magnetoresistance effects in three-terminal devices. (29th February 2016) - Txoperena, Oihana; Casanova, Fèlix
Abstract: Conceiving a simple and trustworthy method to efficiently extract the spin transport properties of any nonmagnetic material is a long-sought goal in spintronics. This is especially ambitious in the case of semiconductors, due to the complications when handling them during the extreme miniaturizations required in many of the well-established techniques. This review is devoted to the evaluation of the recently proposed three-terminal Hanle measurements, with contact sizes far above the nanoscale, which make it appealing and consequently employed in a wide variety of materials. However, the interpretation of the ambiguous results observed in this apparently promising method gives rise to the discovery of other magnetoresistance mechanisms, which coexist with the originally sought spin accumulation in the nonmagnetic material under test. The competition between all these physical scenarios makes an understanding of the data truly challenging.